(untitled) (Confluenţe Bibliologice, 2012)
Costache Parno is one of the ﬁrst well-known Bassarabian musicians who was born and lived in Balti. He did not know neither write nor read, but learned the notes and was the ﬁrst ﬁddler, who taught music at city school, driven by a methodological rules and system. Parno Costache’s life was dedicated to art.